Lipopolysaccharide induces inflammatory cytokines in the pig amnion - Trebichavský, Ilja; Splíchal, Igor; Zahradnícková, Marie; Splíchalová, Alla; Mori, Yasuyuki (Veterinary immunology and immunopathology, 2002)
Inflammatory mediators that are induced by gram-negative bacteria in the course of intrauterine infections threaten successful pregnancy. To compare the effect of two different routes of cytokine induction, bacterial lipopolysaccharide (LPS) was administered in vivo either into the cord vein or into the amniotic cavity of pig fetuses in the second half of gestation for 20 h and cytokines were detected in the amnion.Tumor necrosis factor-alpha (TNF-alpha) and interleukin-8 (IL-8) were induced in the amniotic epithelium after intra-amniotic but not after intra-venous administration of LPS. The presence of IL-8 was confirmed by RT-PCR. In contrast, transforming growth factor-beta1 (TGF-beta1) was expressed constitutively and was found in all samples of the amniotic epithelium. Amniotic fluid contained only minute levels of TNF-alpha. IL-8 levels in amniotic fluid increased after the treatment with LPS and the highest IL-8 levels were found in dead LPS-treated fetuses.
Keywords: Animals; Swine, Miniature; plod; chorioamnionitida; Chorioamnionitis; Female; lipopolysacharidy; Interleukin-8; Transforming Growth Factor beta1; Tumor Necrosis Factor-alpha; ženské pohlaví; Transforming Growth Factor beta; Immunohistochemistry; Fetus; miniaturní prasata; transformující růstový faktor beta; těhotenství; prasata; Swine Diseases; messenger RNA; nádorové buňky kultivované; polymerázová řetězová reakce s reverzní transkripcí; Lipopolysaccharides; transformující růstový faktor beta1; imunohistochemie; RNA, Messenger; interleukin-8; TNF-alfa; Tumor Cells, Cultured; Reverse Transcriptase Polymerase Chain Reaction; nemoci prasat; Swine; amnion; zvířata; Pregnancy; Amnion